Tres mujeres en la administración: Lillian Moller Gilbreth, Mary Parker Follett y Joan Woodward - Paolini, Norma Adela (2016)
This paper aims to pay tribute to three pioneering women in the development of Management studies. It is a summary of the contributions made by these outstanding researchers, while respecting their specific characteristics, according to the different contexts in which they acted and the personal stamp that left a legacy to the discipline. 1. Lillian Moller Gilbreth, a pioneer in the field, she developed with her husband working methods that laid the foundation of Ergonomics. After the death of Lillian Moller her husband continued with the employment and occupation activity, overcoming many obstacles related to feminine gender. 2. Mary Parker Follett, leading researcher, due to her who given their sensitivity, was a pioneer in studies of humanist and social character in organizations. 3. Joan Woodward, well known teacher and researcher, transcended for its relevant and rigorous studies in the manufacturing industry of England, focusing on the impact of technology in its structures.The main purpose is to bring information to the reader in order to give dimension and observe  their  contributions and proposals from a current perspective.